2018
DOI: 10.1051/matecconf/201816202032
|View full text |Cite
|
Sign up to set email alerts
|

Identification and analysis of factors affecting labour productivity in Iraq

Abstract: Productivity is a very important element in the estimation process in construction management. The objective of this research is to identify and analyze the factors which affect labor productivity in construction projects. In this research, 42 effective factors were collected from site survey, interview with engineers and experts, and previous research in the Arab world. These factors are grouped into Nine categories “Workforce, Leadership, Motivation, Supervisors, Safety, Project, Time, Material, and External… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 13 publications
0
12
0
1
Order By: Relevance
“…The barriers to implementing the sustainable piling construction method that significantly affects the Sri Lankan construction industry were identified based on their RIIs that were calculated using Equation 01. According to Khaleel and Nassar (2018), the effect of each barrier group with RII values as Very High (RII > 0.8), High (RII 0.8-0.6), Average (RII -0.6-0.4) and Less (RII < 0.4).…”
Section: Methodsmentioning
confidence: 99%
“…The barriers to implementing the sustainable piling construction method that significantly affects the Sri Lankan construction industry were identified based on their RIIs that were calculated using Equation 01. According to Khaleel and Nassar (2018), the effect of each barrier group with RII values as Very High (RII > 0.8), High (RII 0.8-0.6), Average (RII -0.6-0.4) and Less (RII < 0.4).…”
Section: Methodsmentioning
confidence: 99%
“…The results of their study confirmed the importance of project control experience level and manpower quality in improving labor productivity. Khaleel and Nassar (2018) [24] identified and analysed the critical factors affecting labor productivity in construction projects in Iraq, organizing them into seven groups: manpower, management, motivation, site supervisors, site safety, project schedule and budget, and work resources. Their questionnaire results identified the main factors affecting labor productivity as material availability, weather conditions, holidays, number of working groups, crew experience and age, and revisions to technical drawings and material specifications during the design and execution phases.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Jarkas [22] quantified the impact on construction productivity and established a practical approach to the relationship between relevant buildability factors and the productivity of formwork labour in building floors using a practical approach. Khaleel and Nassar [23] identified and analysed the factors which affect labour productivity in construction projects in the Arab world.…”
Section: Labour Productivity Factorsmentioning
confidence: 99%